Aesculetin exhibited anti-inflammatory activities through inhibiting NF-кB and MAPKs pathway in vitro and in vivo. (5th October 2022) - Wang, Shou-Kai; Chen, Ting-Xiao; Wang, Wei; Xu, Ling-Ling; Zhang, Yu-Qing; Jin, Zhen; Liu, You-Bin; Tang, You-Zhi
Abstract: Ethnopharmacological relevance: Aesculetin (6, 7-dihydroxy-2H-1-benzopyran-2-one) has been reported to exhibit potent anti-inflammatory property both in vitro and in vivo . Aims of this study: In this study, we evaluated the anti-inflammatory effect and investigated underlying molecular mechanisms of aesculetin in LPS-induced RAW264.7 macrophages and DSS-induced colitis. Materials and methods: In this study, the production of NO, TNF-α, and IL-6 were measured to identify the aesculetin with potent anti-inflammatory effect. Then, the underlying anti-inflammatory mechanisms were explored by western blotting in LPS-induced cells. Next, we verify the anti-inflammatory potential of aesculetin in DSS-induced colitis in vivo . The clinical symptoms of colitis, including weight loss, DAI, colon length and MPO activity, and the secretion of TNF-α and IL-6 were evaluated. Finally, Western blot analysis was applied to further investigate underlying mechanism in DSS-induced colitis model. Results: Our studies showed that aesculetin exhibited anti-inflammatory potential by inhibiting NO, TNF-α, and IL-6 production and reducing iNOS and NLRP3 expression in LPS-induced RAW264.7 cells. Mechanically, we found that aesculetin significantly inhibited LPS-induced activation of NF-κB and MAPKs signaling pathways. In DSS-induced mouse model, the colitis-related symptoms were relieved by treatment with aesculetin. Besides, aesculetin also inhibited the secretion of TNF-α and IL-6, and the activation of NF-κB and MAPKs signaling pathways in DSS-induced colitis. Conclusions: The anti-inflammatory effect of aesculetin was connected with its inhibition on the activation of NF-κB and MAPKs signaling pathways both in vitro and in vivo . Therefore, aesculetin was expected to be developed as an anti-inflammatory drug. Graphical abstract: Aesculetin (ECT), one of the main bioactive ingredients of Fraxinus rhynchophylla, could exhibit anti-inflammatory effect by inhibit NF-κB and MAPKs signaling pathways in LPS-induced RAW264.7 cells and DSS-induced colitis mice. Image 1 Highlights: Fraxinus rhynchophylla is usually used as an astringent traditional medicine. Aesculetin is one important active coumarin derivative in Fraxinus rhynchophylla. Anti-inflammatory activities of aesculetin were studied by LPS-induced RAW264.7 cells and DSS-induced colitis mice. This work highlights the anti-inflammatory mechanisms of aesculetin.